Perancangan Prototype Alat Penghapus Papan Tulis Otomatis Dengan Koneksi Bluetooth - KH, Musliadi; Pernando, Yonky (Journal of Digital Ecosystem for Natural Sustainability, 2022)
The advancement of technology has brought innovation in various aspects of life, including the field of education. One area that continues to evolve is educational technology, particularly in the use of tools to enhance more effective learning processes. In this context, this research aims to design and develop a prototype of an automatic whiteboard eraser with Bluetooth connectivity. This study combines microcontroller technology and Bluetooth connectivity to create a device that enables automatic whiteboard erasing. By integrating components such as a DC motor, HC-05 Bluetooth module, and others, this device can be operated through a mobile device connected via Bluetooth. Furthermore, the device is equipped with end-limit settings to stop the eraser at the edge of the whiteboard, along with the use of sensors for monitoring. The outcome of this research is a prototype of an automatic whiteboard eraser that can be easily operated through Bluetooth connectivity. Users can control the device via a mobile application, providing convenience and flexibility in usage. The device is also designed with a focus on safety and efficiency, making it suitable for comfortable use in educational settings. Through testing and evaluation, the device successfully achieves effective and consistent whiteboard erasing. With the integration of Bluetooth connectivity, this device offers a modern solution to facilitate teaching and learning processes. It is hoped that the results of this research will contribute positively to the development of technology-based educational tools and open doors for further advancements in supporting innovative and interactive education.